PRESS STRONG CONCRETE ADDED SHELL OF KEONG SAWAH - Gumilang, Pandu Dimas; Safarisky, Hendramawat Aski; Marwahyudi, Marwahyudi (Universitas Ibn Khaldun Bogor, 2021)
Concrete is a building structure whose development is relatively fast because it is an important part of development. Shells of keong sawah, which are pests for rice plants, can also be used as an added material in making concrete because they contain a large amount of calcium carbonate. This study aims to determine the effect of adding shells of keong sawah on the compressive strength of concrete with a variation of 0% and 15% on the weight of cement. This research was conducted using a cylindrical concrete specimen with a diameter of 15 cm and a height of 30 cm. The results showed that the addition of 15% powder shells of keong sawah had an increase in compressive strength, namely 31.1 MPa when compared to the 0% variation with a compressive strength value of 25.6 MPa. It can be concluded that in this study the addition shells of keong sawah 15% by weight of cement can increase the compressive strength of the concrete.